Study of high-quality superconducting FeSe single crystals: crossover in electronic transport from a metallic to an activated regime above 350 K. (28th August 2015) - Karlsson, S; Strobel, P; Sulpice, A; Marcenat, C; Legendre, M; Gay, F; Pairis, S; Leynaud, O; Toulemonde, P
Abstract: We report the growth of high quality FeSe single crystals using chemical vapor transport based on an AlCl3 /KCl eutectic and their physical properties were fully characterized by magnetic, transport and specific heat measurements. Their critical superconducting temperature at T c ∼ 8.7 K (width < 0.7 K) and structural tetragonal–orthorhombic transition at T s ∼ 85–90 K confirm the values already reported in the literature for similar crystals. In addition, the non-variation of T s under high magnetic field (up to 14 T) determined by magnetic and specific heat measurements indicates that spin fluctuations are not directly involved in the structural transition. Finally, high temperature electrical resistivity measurements up to 600 K evidence a maximum around 350 K. The origin of this crossover from metallic behavior at low temperature to a semiconducting-like regime at high temperature is discussed and could be associated with a change of carrier density above 350 K. On the other hand, the tentative growth of Te-substituted Fe(Se1− x Te x ) crystals using the same growth method resulted in crystals with x (Te) < 1% and a slightly lower T c compared to pure FeSe ones, which may be related to transition metal–chalcogen non-stoichiometry. Finally, Cr doping at the Fe site was also attempted. In contrast to previous reports in the literature, our results suggest that Cr does not substitute for Fe in the FeSe crystal but agglomerates in Cr-rich (Cr, Fe)Se2 inclusions, and T c of these (Fe1− x Cr x )Se crystals is not increased, but slightly decreased in comparison to stoichiometric FeSe crystals.